Combining a CDK4/6 Inhibitor With Pemetrexed Inhibits Cell Proliferation and Metastasis in Human Lung Adenocarcinoma - Ke, Yuan; Liao, Cheng-Gong; Zhao, Zheng-Qing; Li, Xiao-Min; Lin, Rong-Jie; Yang, Long; Zhang, He-Long; Kong, Ling-Min (Frontiers in Oncology, 2022)
Background: Recent clinical trials of cyclin-dependent kinase 4/6 inhibitors (CDK4/6i) in human lung adenocarcinoma (LUAD) have not achieved satisfactory results. The disappointing results of single-drug treatments have prompted studies on the effect of combination therapies of CDK4/6i with other drugs. We aimed to test the anti-tumor effect of ribociclib (a CDK4/6i) combined with pemetrexed on LUAD and the potential mechanisms. Methods: Cell lines were exposed to ribociclib and pemetrexed at different doses. Antitumor effects were measured using growth inhibition. Cell cycle distribution and apoptosis were evaluated using flow cytometry. Cell migration and invasion were measured using wound healing and transwell invasion assays, respectively. The expression levels of proteins were analyzed using western blotting. Mice xenograft models were used for validation in vivo. Results: Synergism was associated with a combination of cell cycle effects from both agents. Cell cycle analysis revealed that pemetrexed blocked cells in the S phase, whereas ribociclib arrested cells in the G1 phase. Concomitant treatment with pemetrexed and ribociclib resulted in a significantly stronger antitumor ability than treatment alone. We also found that ribociclib markedly enhanced the pro-apoptotic activity of pemetrexed via the caspase/bcl-2 signaling pathway. In addition, our results showed that combination treatment with ribociclib and pemetrexed significantly inhibits the migration and invasion of LUAD cells. Conclusions: Combining ribociclib and pemetrexed showed a powerful ability to inhibit cancer proliferation, invasion, and metastasis, and it holds potential as a novel effective combinative therapy for patients with LUAD.